1998
DOI: 10.1029/97wr03608
|View full text |Cite
|
Sign up to set email alerts
|

Concentration fluctuations and dilution in aquifers

Abstract: Abstract. The concentration of solute undergoing advection and local dispersion in a random hydraulic conductivity field is analyzed to quantify its variability and dilution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
104
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(111 citation statements)
references
References 22 publications
6
104
1
Order By: Relevance
“…Therefore, the assessment of the state of an aquifer, based only on low order (statistical) moments, provides a picture which is at best incomplete in the context of risk and/or vulnerability assessment. In particular, Kapoor and Kitanidis (1998) and Fiori and Dagan (2000) showed that in unbounded formations under uniform mean flow conditions the coefficient of variation of the solute concentration is a non-monotonic function of travel time and reaches a maximum at a time linked with the time scale of processes characterizing pore-scale dispersion. In this sense, the interest lays in the knowledge of the extreme values where quantities such as concentration, travel time and/or trajectories can attain in a region of investigation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the assessment of the state of an aquifer, based only on low order (statistical) moments, provides a picture which is at best incomplete in the context of risk and/or vulnerability assessment. In particular, Kapoor and Kitanidis (1998) and Fiori and Dagan (2000) showed that in unbounded formations under uniform mean flow conditions the coefficient of variation of the solute concentration is a non-monotonic function of travel time and reaches a maximum at a time linked with the time scale of processes characterizing pore-scale dispersion. In this sense, the interest lays in the knowledge of the extreme values where quantities such as concentration, travel time and/or trajectories can attain in a region of investigation.…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the work of Dagan (1989), several analytical solutions have been proposed rendering space-time distributions of (ensemble) mean and variance-covariance of concentrations or trajectories and time-of-residence of conservative solutes in multidimensional porous systems (Cvetkovic et al 1992;Kapoor and Gelhar 1994;Kapoor and Kitanidis 1998;Fiori and Dagan 2000;Vanderborght 2001;Guadagnini et al 2003;Sanchez-Vila and Guadagnini 2005;Riva et al 2006). All of these solutions rely on (different flavors of) the perturbation theory to provide approximations of governing equations and associated solutions.…”
Section: Introductionmentioning
confidence: 99%
“…One can develop an evolution equation for the productc AγcBγ , which is frequently done. [50][51][52] Although this shows that the evolution ofc AγcBγ depends upon the scalar dissipation rate, this in itself is not entirely helpful because one does not know the scalar dissipation rate a priori either. Additionally, the expression forc AγcBγ exhibits the typical hierarchy problem for nonlinear equations; thus, it is not technically possible to close and expression for this product without significant approximations.…”
Section: A Localization Of the Closure Problemsmentioning
confidence: 99%
“…Mixing processes in groundwater have not been investigated systematically, although their existence was noted in passing by Kitanidis [1994] and Kapoor and Kitanidis [1998a]. However, mixing phenomena, being important much earlier in the spreading of a solute plume than is dilution, create the complex plume-groundwater interface that enhances local dispersion processes [Ottino, 1991;Kitanidis, 1994;Kapoor and Kitanidis, 1998a].…”
Section: Paper Number 98wr02535mentioning
confidence: 99%
“…However, mixing phenomena, being important much earlier in the spreading of a solute plume than is dilution, create the complex plume-groundwater interface that enhances local dispersion processes [Ottino, 1991;Kitanidis, 1994;Kapoor and Kitanidis, 1998a]. In this paper we discuss basic concepts of plume mixing into groundwater, following the conceptual design of Ottino [1989, chapters 2 and 4; 1990], who considered fluid flows that were engineered to enhance mixing.…”
Section: Paper Number 98wr02535mentioning
confidence: 99%